2006
DOI: 10.1080/02652030600904894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking on enrofloxacin residues in chicken tissue

Abstract: The aim of this study was to determine the effect of different cooking processes (microwaving, roasting, boiling, grilling and frying) on naturally incurred enrofloxacin residues in chicken muscle. Enrofloxacin and its metabolite, ciprofloxacin, were analysed using a validated LC-MS method with limits of detection (LOD) and quantification (LOQ), respectively, of 2 and 5 ng g-1 quinolones in muscle samples. The method was shown to be linear over the range 5-500 ng g-1. Mean intra-day relative standard deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 13 publications
5
50
0
Order By: Relevance
“…Accordingly, in our work (Table 3), citrate buffer/MeOH (75:25 v/v) extraction was the selected procedure for extracting OTC and its degradation compounds from chicken muscle and pig muscle samples since that mixture gave the greatest recoveries for each of the analyzed compounds. The findings reported here are consistent with previous studies in which thermal treatments were shown to reduce the concentration of veterinary drug residues in foods; therefore decreasing the possible toxic effects of these compounds to consumers (Fedeniuk et al 1996;Kuhne et al 2001a, b;Gratacós-Cubarsí et al 2007;Furusawa and Hanabusa 2001;Javadi 2011;Lolo et al 2006). At the same time, the thermal treatments resulted in the formation of the corresponding apoOTCs in all treated meat samples.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Accordingly, in our work (Table 3), citrate buffer/MeOH (75:25 v/v) extraction was the selected procedure for extracting OTC and its degradation compounds from chicken muscle and pig muscle samples since that mixture gave the greatest recoveries for each of the analyzed compounds. The findings reported here are consistent with previous studies in which thermal treatments were shown to reduce the concentration of veterinary drug residues in foods; therefore decreasing the possible toxic effects of these compounds to consumers (Fedeniuk et al 1996;Kuhne et al 2001a, b;Gratacós-Cubarsí et al 2007;Furusawa and Hanabusa 2001;Javadi 2011;Lolo et al 2006). At the same time, the thermal treatments resulted in the formation of the corresponding apoOTCs in all treated meat samples.…”
Section: Discussionsupporting
confidence: 82%
“…Halling-Sorensen et al 2002 reported that the degradation products of OTC, such as 4-epi-oxytetracycline (EOTC), α-Apo-OTC and β-Apo-OTC exhibited greater toxicity (EC50) compared with the parent compound. Several studies indicate that thermal treatments reduce the concentration of various veterinary drug residues in foods and thus decrease the potential toxic effects of these compounds on the consumer (Furusawa and Hanabusa 2001;Javadi 2011;O'Brien et al 1981;Rose et al 1996;Kuhne et al 2001a, b;Lolo et al 2006). However, in these studies only the degradation of the parent drug was evaluated and the toxic effects of the degradation products of the parent drug was not studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the initial concentrations of all tested antibiotics diminished to variable degrees after heat treatments (Figure 1). These results are generally in good agreement by drug classes with previous studies (Rose et al, 1996;Moats, 1999;Podhorniak et al, 1999;van Egmond, 2000;Kuhne et al, 2001a,b;Lolo et al, 2006) confirming that thermal treatments may reduce the concentration of veterinary drug residues in foods and thereby might decrease possible pharmacological and/or toxic effects of these compounds. Higher percentage reductions were apparent at higher temperatures showing up to 99% reduction at 121 °C in contrast to 54.4% at 100 °C for TC and most other antibiotics (Figure 1), indicating that the degree of reduction was associated with heating temperature.…”
Section: Structural Degradation By Peak Areasupporting
confidence: 80%
“…The Ames test evaluates the mutagenic potential of chemicals by studying their effects on one or more histidine-requiring strains of Salmonella typhymurium in the absence and presence of a liver metabolizing system (S9 microsome). Salmonella strains TA98 and TA100 are sensitive strains that are commonly used for detection of specific frame-shift point mutations and base pair mutations respectively (Lolo et al, 2006). A compound was considered a mutagen if the tested sample produced a response, which was at least twice as high as the one found with the negative control (Maron and Ames, 1983) and a doseeffect relationship was observed.…”
Section: Mutagenicity (Ames) Testmentioning
confidence: 99%
“…Deproteinization and extraction with acetonitrile, without later steps, permits the HPLC/MS-MS analysis of fluoroquinolones [38,39] or steroids [40] and this procedure has been used in our laboratory for some years.…”
Section: Methodology Developmentmentioning
confidence: 99%